1980
DOI: 10.1002/1097-0142(19800215)45:4<780::aid-cncr2820450428>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Serum β2-microglobulin in patients with bronchial carcinoma and controls

Abstract: We measured serum levels of P,-microglobulin in 467 patients mainly with suspected pulmonary malignancy. By applying serum concentrations of 3.0 mgiliter as the normal upper limit, we found elevated levels in 21% of the patients with verified bronchial carcinoma (n = 230) and in 11% of the patients with lung diseases of infectious, inflammatory, or other origins but without proven malignancy. A rise in serum µglobulin levels with advancing age was demonstrated in cancer patients and controls. No significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…The basic data relating to these three tumour types are shown in Table 11. The awareness that serum creatinine levels can influence 02-m levels is appreciated by all investigators, but the age-dependent rise of 02-m, and its tendency to rise more steeply in the elderly [38] are taken into account only by some investigators.…”
Section: Variations Of Serum 02-m I N Adenocarcinomamentioning
confidence: 98%
See 1 more Smart Citation
“…The basic data relating to these three tumour types are shown in Table 11. The awareness that serum creatinine levels can influence 02-m levels is appreciated by all investigators, but the age-dependent rise of 02-m, and its tendency to rise more steeply in the elderly [38] are taken into account only by some investigators.…”
Section: Variations Of Serum 02-m I N Adenocarcinomamentioning
confidence: 98%
“…Shuster et al [29], using a serum 02-m of 3 mg/liter as a cut-off, found 33% of patients with lung malignancies to be above this level. In a study of 460 patients suspected of having lung cancer, Hallgren et a1 [38] observed that 21% of 230 patients with lung cancer had a serum 02-m > 3 mg/liter; 11 % of patients with various nonmalignant conditions of the lungs also had serum 02-m > 3 mg/liter. There did not appear to be any significant difference between the different types of lung cancer.…”
Section: Lung Cancermentioning
confidence: 99%
“…Multiple lines of evidence show that β2-m is involved in cancer and other human malignancies. Increased synthesis and release of β2-m, as indicated by elevated serum, plasma, or urine β2-m concentration, occurs in several malignant diseases, including prostate cancer, lung cancer, breast cancer, renal cell carcinoma (RCC), gastrointestinal and nasopharyngeal cancers, hepatocellular carcinoma, ovarian cancer, multiple myeloma, and lymphocytic malignancies such as non-Hodgkin’s lymphoma, in addition to autoimmune and chronic infectious diseases [19, 21-29, 49, 50]. Furthermore, a number of studies have demonstrated that the level of serum β2-m is one of the most important independent prognostic factors and survival predictors for some tumors including RCC, multiple myeloma, and T-cell leukemia [22, 24, 28].…”
Section: β2-m As a Biomarker For Cancersmentioning
confidence: 99%
“…In humans, also known as component of the cells associated with the heavy chains of major histocompatibility complex (MHC) class I molecules, the β 2 -microglobulin polypeptide is encoded by the B2M gene [1,2]. β2M levels are elevated in many tumors, including small cell lung cancer, T cell leukemia, breast cancer, renal cell carcinoma (RCC), prostate cancer, gastrointestinal cancers, hepatocellular carcinoma, ovarian cancer, multiple myeloma, and lymphocytic malignancies such as non-Hodgkin's lymphoma [3][4][5][6][7][8][9][10][11]. It also associated with an enhanced rate of cell production or disruption, viral infections such as cytomegalovirus (CMV), and some conditions that activate the immune system, such as autoimmune disorders and inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%